Outcome of Down syndrome associated acute lymphoblastic leukaemia treated on a contemporary protocol. (15th January 2014) - Patrick, Katharine; Wade, Rachel; Goulden, Nicholas; Rowntree, Clare; Hough, Rachael; Moorman, Anthony V; Mitchell, Christopher D; Vora, Ajay
Summary We report the outcome for children and young people with Down syndrome‐associated acute lymphoblastic leukaemia (DS‐ALL) treated on a contemporary protocol. Compared with non‐DS ALL, patients with DS‐ALL had an inferior event‐free survival (65·6% vs. 87·7% at 5 years; P < 0·00005) and overall survival (70·0% vs. 92·2%; P < 0·00005). Excess treatment‐related mortality – was primarily responsible for the worse outcomes for DS‐ALL (21·6% at 5 years, vs. 3·3%, P < 0·00005). Minimal residual disease (MRD) risk status was highly discriminant for relapse in DS patients with 0/28 relapses in the MRD low risk group.